The idea of mature mind in Kant’s philosophy (Actual Problems of Mind, 2021)
The article represented the reconstruction of the idea of mind, which formulated by Kant in his critical philosophy. The author rationalizes the position, that Kant as Enlightenment’s thinker reveals various aspects of his vision of the mature mind of the finite being – the mind of «adult» man. It is maintained that for Kant the concept of mind is the main concept of his critical philosophy at all and that in various works at different times he reveals certain philosophical aspects of the system phenomenon as a mature mind. Using political and legal metaphors, Kant, by analogy with legal systematicity, presents the mind as an ordered system, with a clear separation of the lawful and unlawful usage of the subject’s individual higher cognitive powers (such as understanding, judgment, reason) within their competence. The author demarcates three essential features of a mature mind in Kant’s explication: (1) free; (2) intersubjective; (3) autonomous. Each of these aspects has undergone a certain evolution, that represents the evolution of Kant’s philosophy in general: from a purely enlightening affirmation to the emancipation of reason (liberation from superstitions) to the idea of autonomous self-legitimate mind acting as a judge and arbiter within a holistic «critical enterprise». The author emphasizes that for Kant, the following maxim of free from superstitions mode of thought means that the mind is in an active state, without that state the mind cannot be a legislator either in the field of knowledge or practice. In this regard, a «revolutionary change in the way of thinking» (the Copernican revolution) in Kant’s theoretical and practical philosophy is considered as a consequence of his Enlightenment explication of mind. The article focuses also on Kant’s explication of the public use of mind and the idea of a broadened way of thinking, his critique of the position of logical selfishness and his conceptualization of logical pluralism based on the idea of the universal mind.
Keywords: Kant, mature mind, critical philosophy, Enlightenment, autonomy.